A Statistical Study of Gender Differences in Internet Use (Students of Computer Science Faculty, Kabul University) - Shahidzai, Amir Kuror; Zarinkhail, Mohammad Shuaib (Journal of Natural Sciences – Kabul University, 2023)
The goal of the study was to see if there was any gender difference in Internet usage among students of Computer Science Faculty. Respondents (200) were chosen from the student population across the faculty using a stratified random sampling procedure. The study employed a descriptive survey research approach. The participants were given a 14-item questionnaire to fill out in order to collect the data. The SPSS program was used to examine the data. According to the study, the majority of the participants (163) had Internet connection. The Internet was found to be gender-neutral in terms of accessibility. Gender disparities in Internet usage habits were statistically significant and were analyzed on news, sports, and social media sites.